Pharmacokinetics of Sildenafil in Patients with a Left Ventricular Assist Device: A Word of Caution. Issue 5 (July 2019) - Sabato, Leah A.; Johnson, Daniel C.; Haglund, Nicholas; Keebler, Mary; Cox, Zachary L.
Abstract : We compared maximal plasma concentrations ( C max ) of sildenafil and metabolite n -desmethyl sildenafil in 12 inpatients with left ventricular assist devices (LVADs) on sildenafil (60 mg/day) to the reference range. Sildenafil C max (156.8 ± 124.5 ng/ml) was elevated in 66% of patients, with a two to fivefold increase over the upper limit of the reference range in 25% of patients. Metabolite C max (133.3 ± 102.0 ng/ml) was elevated in 75% of patients, with a three to sevenfold increase over the upper limit of the reference range in 40% of patients. Patients with heart failure and LVADs are at increased risk of concentrated-related sildenafil adverse events.